RELATIONSHIP OF MOTIVATION AND STUDENT LEARNING OUTCOMES IN COOPERATIVE LEARNING IN SCIENTIFIC LEARNING IN STATE 15 PADANG MIDDLE SCHOOL - mesa huriatun nazmi; Usmeldi Usmeldi (Universe, 2020)
This study aims to identify and describe the relationship of motivation and student learning outcome in cooperative learning in science subjects in SMP Negeri 15 Padang. This is a descriptive study using a correlation approach. The population of this study was students of class VII SMP Negeri 15 Padang consisting of 7 (seven) classes totaling 224 students. The sample consisted of 26 students in grade VII 1. Student motivation data were obtained through a questionnaire and data on learning outcomes were obtained through students' UH grades. The questionnaire used was a questionnaire that had been declared valid and reliable. Based on the analysis shows that the data analysis of the research results obtained correlation coefficient r count> r table (0.478> 0.388) at a significant level of 5% and has a contribution of 23%. The conclusion of this study is that there is a positive and significant relationship between learning motivation and student learning outcomes in cooperative learning in science subjects in junior high school 15 Padang.